Utilizing Resources of Drug Information among Community Pharmacists in Benghazi and the Surroundings (Razi Medical Journal, 2025)
One of the fundamental professional duties of all pharmacists is to provide Drug Information (DI). DI refers to the finding, application, and administration of information regarding the usage of drugs. Drug information includes everything from dosage and side effects to identification, cost, and pharmacokinetics. You may also need information about the body, health, or diseases to better utilize the drug information. The focus is on understanding how pharmacists’ access and apply information regarding drug use, interactions, side effects, and safety, especially during pregnancy and lactation. Additionally, the study explores pharmacists' confidence in digital and traditional DI sources and their critical role in disseminating drug information to the public. Aiming to identify common DI needs, frequently used resources, and pharmacists' trust in available information. This cross-sectional descriptive study investigates DI sources utilized by community pharmacists in Benghazi and its suburbs. It examines the types of DI resources they most frequently consult and the nature of questions they encounter in practice. The focus is on understanding how pharmacists’ access and apply information regarding drug use, interactions, side effects, and safety, especially during pregnancy and lactation. Additionally, the study explores pharmacists' confidence in digital and traditional DI sources and their critical role in disseminating drug information to the public. Aiming to identify common DI needs, frequently used resources, and pharmacists' trust in available information. Regarding data collection, it is conducted between June and October 2024 via an online survey distributed through social media platforms. The study engaged 252 pharmacists, primarily from urban areas like Benghazi and surrounding areas. The results show a predominantly young, female workforce with a high reliance on online DI resources, particularly Google, Medscape, and Drugs.com; moreover, tertiary resources like the "Drug Information Handbook" and "Basic and Clinical Pharmacology" are also referenced. Despite the scarcity of comprehensive textbooks in most pharmacies, 96% of pharmacists used the internet for drug-related inquiries, with 78% trusting this information for patient advice. Key questions pertained to drug safety during pregnancy, dosages, and drug interactions. In conclusion, the findings highlight the essential role community pharmacists play in providing drug information to the public, as well as the need for enhanced access to and training in reliable DI resources to support safe, informed pharmaceutical care in Libyan pharmacies.
Keywords: Drug Information Resources, Benghazi And Its Suburbs, Community Pharmacy, Drug Safety